The Impact of Entry Regulation on Total Welfare: A Policy Experiment - An-Hsiang Liu; Ralph Siebert; Christine Zulehner (Center for Economic Studies and ifo Institute (CESifo), 2013)
This paper evaluates how different lengths of entry regulation impact market structure and market performance using a dynamic structural model. We formulate an oligopoly model in the tradition of Ericson and Pakes (1995) and allow entry costs to vary over time. Firms have the opportunity to produce multiple products, and decide when to enter a market, followed by production and exit decisions. Using quarterly firm-level data on the static random access memory industry from 1974 to 2003, we find that entry costs decline by more than 90% within the first three years. Our policy experiments provide evidence that the duration of entry regulation has a negative impact on consumer surplus. We also find that entry protection increases total surplus if the protection duration is either sufficiently short or sufficiently long. If entry protection duration is short, the increase in monopolist's profits and entry cost saving dominate the reduction in consumer welfare, which affects total welfare positively. If protection duration is long, dynamic efficiency gains, i.e., the delay of subsequent entry and savings on entry costs impact total welfare positively.
Keywords: C10; L10; L60; O30; 330; development costs; entry costs; dynamic oligopoly; entry regulation; innovation; intellectual property rights; market entry; market structure; policy experiment; semiconductor industry